Detrimental activation of AhR pathway in cancer: an overview of therapeutic strategies. (June 2021) - Leclerc, Delphine; Staats Pires, Ananda Christina; Guillemin, Gilles J; Gilot, David
Highlights: AhR is an ubiquitous transcription factor activated by a broad spectrum of endogenous and exogenous ligands. Sustained AhR activation promotes immune regulation, cell dedifferentiation and therapy resistance in several cancers. Targeting the AhR-signalling pathway might restore therapy efficiency. Evaluation of AhR activity in patients' plasma might be a potential associated companion biomarker. Abstract : Sustained transcriptional activation of the aryl hydrocarbon receptor (AhR) promotes tumour growth and impairs the immune defence, at least for cutaneous melanoma and glioma. AhR ligands are produced by the tumour microenvironment (TME) and by the tumour itself (intracrine). The recent identification of interleukin-4-induced-1 (IL4I1), a parallel pathway to indoleamine 2 3-dioxygenase 1 (IDO1)/ tryptophan 2, 3-dioxygenase (TDO), and its ability to generate AhR ligands, confirms that a complete inhibition of AhR ligand production might be difficult to reach. Here, we have focused on recent discoveries explaining the large varieties of AhR ligands and the functional consequences in terms of cancer cell plasticity and consecutive therapy resistance. We also examined therapeutic strategies targeting the AhR signalling pathway and their possible adverse effects. Since the end of 2019, two phase I clinical trials have investigated the ability of the AhR antagonist to 'reset' the immune system and re-sensitize the cancer cells to therapies by preventing their dedifferentiation.